Society Rolls Out New Certification. (Computer (00189162), 2008)
The article offers information on the Certified Software Development Associate (CSDA) certification created by the IEEE Computer Society for those entering the software development profession. The certification takes a broad view of software development and validates knowledge of the foundations of computer science, mathematics and engineering. Core software engineering principles covered include software construction, design and testing. The CSDA examination focuses on key concepts addressed in the books "The Guide to the Software Engineering Body of Knowledge" (SWEBOK) and "Software Engineering 2004: Curriculum Guidelines for Undergraduate Degree Programs in Software Engineering."